(untitled) (Fiep Bulletin - online, 2017)
Historically, the practice of teacher of physical education was associated with a number of educational trends that directly or indirectly design methodological framework of the teacher and do in the classroom. Today, despite skeptical about the possibility of change through the daring to try, believe that the flow of the feasibility of cut of time with the shackles that trap in the practice outdated and meaningless concepts, it becomes increasingly solid and known in the school. The teacher of Physical Education, today, realizes the close relationship that exists between their practice and reflection so that it can, finally, comes the compromise teaching, facilitating exchanges of experiences and understanding of real respect for others, in addition to the awakening relevance of the pleasure of teaching based on the willingness to learn and to grow with satisfaction. To that end, it was of key importance remarks made in state schools, the southern city of Manaus, and goodwill of teachers of Physical Education who agreed to participate in this study.